BIOGAS PRODUCTION KINETIC FROM VINASSE WASTE IN BATCH MODE ANAEROBIC DIGESTION - Budiyono, Budiyono; Syaichurrozi, Iqbal; Sumardiono, Siswo (Malaysian Journal of Science, 2013)
Bottom product of distillation unit from bioethanol industry is often called as vinasse waste. Anaerobic treatment is one of good choice to convert vinasse into biogas. The purpose of this research was to study the biogas production kinetc from vinasse waste in batch mode anaerobic digestion. The kinetic model of biogas production was developed through modified Gompertz equation. Meanwhile, the kinetic of biodegradability of organic material was developed based on first order kinetic reaction. The researh resulted the kineticconstant of biogasproduction were biogas production potential (A),maximum biogas production rate (U), and minimum time to produce biogas (Î») of83,982 mL/(kg COD), 19,71 mL/(kg COD.day), and1.004 days, respectively. Kinetic constant of organic biodegradability material (k) was-0,059day-1 . Kinetic model could be used to design volume of batch digesteranaerobic with the formula Vdigester = 3 * ym (1-exp(-k*t)) * m. (Keywords : batch mode, biogas production, COD/N, kinetic, vinasse, bioethanol industry)